KLASIFIKASI KELAS KONJUGASI GRUP PERMUTASI PADA n UNSUR (S_n) - Ana Diana Silvana Bimolo; Nugraha K. F. Dethan; Fitriani (Journal of Mathematics Theory and Applications, 2024)
Conjugate classes partition the members of a group into mutually exclusive subsets, which can be used to classify the group. For example, conjugate classes can be used to show that two groups are not isomorphic. In this study the author will classify the conjugation class of the permutation group elements . This research uses a literature study method where the author studies the properties, theorems related to conjugation classes and permutation groups. The results obtained from this research are that the conjugation class of a permutation in is determined by its cycle type, namely the partition of with these conjugation classes, namely conjugation classes containing permutations in that have the same cycle type. The number of conjugation classes is equal to the number of cycle types in . Keywords: permutation group, conjugation class.